A Hybrid Peptide PTS that Facilitates Transmembrane Delivery and Its Application for the Rapid In vivo Imaging via Near-Infrared Fluorescence Imaging - Yan, Xuejiao; Wu, Guoqiu; Qu, Qingrong; Fan, Xiaobo; Xu, Xudong; Liu, Naifeng (Frontiers in Pharmacology, 2016)
Background and purpose: Intravital imaging provides invaluable readouts for clinical diagnoses and therapies and shows great potential in the design of individualized drug dosage regimes. Ts is a mammalian free cell membrane-penetrating peptide. This study aimed to introduce a novel approach to the design of a cancer-selective peptide on the basis of a membrane-penetrating peptide and to explore its potential as a carrier of medical substances. Experimental approach: Ts was linked with a αvβ3-binding peptide P1c to create a hybrid referred to as PTS. The hybrid was labeled with an FITC or Cy5.5 as an imaging indicator to evaluate its in vitro and in vivo bioactivity. Key results: Hemolysis tests proved that in comparison with Ts, PTS caused similar or even less leakage of human erythrocytes at concentrations of up to 1 mmol/L. Flow cytometry assay and confocal microscopy demonstrated the following. 1) P1c alone could target and mostly halt at the cancer cell membrane. 2) Ts alone could not bind to the membrane sufficiently. 3) P1c greatly enhanced the binding affinity of PTS with MDA-MB-231 breast cancer cells that upregulated αvβ3. 4) Ts conferred PTS with the ability to traverse a cell membrane and thus facilitate the transmembrane delivery of imaging probes. In vivo near-infrared fluorescence (NIRF) imaging demonstrated that the imaging probes were rapidly concentrated in a MDA-MB-231 tumor tissue within 1 h after intravenous injection. Conclusions and implications: PTS exhibited the capability of targeting specific tumors and greatly facilitating the transmembrane delivery of imaging probes.